Reverse Channel Design: Profitability vs. Environmental Benefits - Lan Wang; Gangshu Cai; Andy Tsay; Asoo Vaharia (Sustainability in Logistics and Supply Chain Management: New Designs and Strategies. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 21, 2015)
Environmental issues are a growing priority in supply chain management, which has heightened the interest in remanufacturing. A key attribute of a remanufacturing strategy is the division of labor in the reverse channel, especially whether the remanufacturing should be performed in-house or outsourced to a third party. We investigate this decision for a retailer who accepts returns of a remanufacturable product. Our formulation considers the relative cost-effectiveness of the two approaches, uncertainty in the input quality of the collected/returned used products, consumer willingness- to-pay for remanufactured product, and the extent to which the remanufactured product cannibalizes demand for new product. Our analysis predicts the retailer's propensity to remanufacture, which provides a metric of the environmental impact of each strategy.
10419/209190; https://econpapers.repec.org/RePEc:zbw:hiclpr:21
Keywords: 650; Reverse Channel Design; Remanufacturing; Outsourcing; Environmental Impact